Roman, fais-moi frissonner de peur et de… plaisir ! Le vampire dans le roman contemporain pour adolescents - Atzenhoffer, Régine (Romanica Silesiana)
The vampire, represented in various media forms, has always scared or fascinated people. Dracula’s current descendants have become a “consumer good” ; the vampire figure is now displayed for commercial purposes, which are profitable both for publishing houses and television productions. In contemporary children’s literature which blends sentimental and paranormal events, vampires once so scary, shiver in fear in front of some of their counterparts. Fear is no longer the sole privilege of the bloodsuckers’ victims ; novels for young adults are populated with living dead who are no longer the sole embodiment of loathsome otherness. Capable of both loving and suffering, they feel fear like mere mortals. Vampires, once awfully stressful and intimidating characters, now shiver in fear in front of some of their counterparts. This is quite an unprecedented turn of events ! Key words : vampires, fear, novels for teenagers